2021
DOI: 10.1021/acs.chemmater.1c02439
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Quantification of Geometric Diversity in Metal–Organic Frameworks

Abstract: With ever-growing numbers of metal−organic framework (MOF) materials being reported, new computational approaches are required for a quantitative understanding of structure−property correlations in MOFs. Here, we show how structural coarse-graining and embedding ("unsupervised learning") schemes can together give new insights into the geometric diversity of MOF structures. Based on a curated data set of 1262 reported experimental structures, we automatically generate coarse-grained and rescaled representations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…SOAP descriptors, on the other hand, do encode the chemical nature of the MOF backbone in the form of atomic neighbor environments within a cut-off radius of, typically, 4–8 Å. They are effective at capturing local chemical information, such as chemical bonds, interatomic/intermolecular interactions, and, generally, densely packed systems. , However, it has been shown that SOAP descriptors fail to capture long-range order, such as molecular packing . Furthermore, we show below that neither SOAP descriptors nor the pore descriptors on their own are effective at encoding the pore space within a MOF for the prediction of its performance in trace CH 3 I capture.…”
Section: Resultsmentioning
confidence: 74%
“…SOAP descriptors, on the other hand, do encode the chemical nature of the MOF backbone in the form of atomic neighbor environments within a cut-off radius of, typically, 4–8 Å. They are effective at capturing local chemical information, such as chemical bonds, interatomic/intermolecular interactions, and, generally, densely packed systems. , However, it has been shown that SOAP descriptors fail to capture long-range order, such as molecular packing . Furthermore, we show below that neither SOAP descriptors nor the pore descriptors on their own are effective at encoding the pore space within a MOF for the prediction of its performance in trace CH 3 I capture.…”
Section: Resultsmentioning
confidence: 74%
“…We have previously shown that cg-ML models enable unsupervised learning in this domain, by visualising structural relationships between ZIFs and inorganic AB 2 networks. 12 Our present work now shows that energetics in Zn(Im) 2 (where Im = imidazolate) can be described, to useful accuracy, by supervised cg-ML models. Our study complements wider-ranging activities on cg force-field development, 13 and at the same time it addresses general questions about the nature of hybrid framework materials.…”
mentioning
confidence: 62%
“…The term refers to the coarse-grain modeling approach, which involves simplification of complex atomic systems, e.g., reducing the number of degrees of freedom by representing groups of atoms as a single pseudoatom. Similar techniques have been applied to quantify MOF diversity , (in an unsupervised manner) and to establish structure–property relationships in a specific class of hybrid materials (zeolitic imidazolate frameworks); the PolymerGNN architecture, which introduces monomer units as molecular graphs, is also worth mentioning. In a recent study, coarse-grained representation was used for generating novel MOF structures within diffusion models.…”
Section: Resultsmentioning
confidence: 99%